Zakat as an Obligatory System and its Implications for Social Psychology of Society (Social Tafsīr of Sūrah Al-Tawbah: 103) - Abdul Wahid Al-Faizin; Taqiyah Dinda Insani; Tika Widiastuti (International Journal of Zakat, 2017)
In the current literature, the study of the collective benefits of Zakat is more emphasized on the material economic aspects by using modern economic tools. Meanwhile, Zakat has a significant social role in the community. Therefore, Allah mentions in Qur'an the command of Zakat and prayer together as much as 22 times. It shows that the role of Zakat socially in human relationships with each other is comparable to the relationship with God. This paper will try to explore and analyze the social role (Social Psychology) of Zakat as an obligatory system from Sūrah al-Tawbah: 103. The method used in this paper is a qualitative method by using content analysis that combines tafsīr bi al-ra’yi with tafsīr bi al-ma’thūr. By using social tafsīr, it is found that Zakat should be an obligatory system and its management must be done centrally by the government. BAZNAS can be a representation of the government to perform the task. Then, it will result in the creation of equal degree and status between mustahiq and muzakki. Meanwhile, the implication of Zakat in the context of social interaction of the society is the creation of tranquility, security, and harmony for the whole society. Keywords: Zakat, Social Tafsīr, Social Psychology